2019
DOI: 10.1042/bsr20181464
|View full text |Cite
|
Sign up to set email alerts
|

Light-exposure at night impairs mouse ovary development via cell apoptosis and DNA damage

Abstract: The alternation of light and dark rhythm causes a series of physiological, biochemical and metabolic changes in animals, which also alters the growth and development of animals, and feeding, migration, reproduction and other behavioral activities. In recent years, many studies have reported the effects of long-term (more than 6 weeks) illumination on ovarian growth and development. In the present study, we observed the damage, repair and apoptosis of ovarian DNA in a short period of illumination. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Changes in the light cycle may regulate seasonal reproduction in birds by regulating the synthesis and release of hypothalamic and pituitary secretions [ 14 ]. In a study, 24 h of light exposure led to a reduction in the total number of ovarian follicles in mice and downregulation of circadian rhythm-related genes within a short period of time (less than 2 weeks), and changes in serum sex hormone levels were also be detected after 24 h, including increased concentrations of LH, FSH, and E2 (estradiol) and a decreased concentration of PROG (progesterone) [ 15 ]. Studies have shown that hens exposed to light for an extended period exhibit higher plasma levels of FSH and LH before laying eggs and that the expression levels of FSH and LH genes are increased [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the light cycle may regulate seasonal reproduction in birds by regulating the synthesis and release of hypothalamic and pituitary secretions [ 14 ]. In a study, 24 h of light exposure led to a reduction in the total number of ovarian follicles in mice and downregulation of circadian rhythm-related genes within a short period of time (less than 2 weeks), and changes in serum sex hormone levels were also be detected after 24 h, including increased concentrations of LH, FSH, and E2 (estradiol) and a decreased concentration of PROG (progesterone) [ 15 ]. Studies have shown that hens exposed to light for an extended period exhibit higher plasma levels of FSH and LH before laying eggs and that the expression levels of FSH and LH genes are increased [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that oxidative stress inhibits follicular development and reduces the feed intake of laying hens, affecting the secretion of gonadotropin in the hypothalamus [ 14 ]. It can directly affect ovarian function and inhibit follicular development [ 15 ], but the mechanism is not clear. To date, the influence of oxidative stress induced by light stress on chicken ovarian function and follicular development has been rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…All primers were synthesized by Servicebio Technology Company (Wuhan, China). The PCR program [ 22 ] was set as: 10 min at 95°C, followed by 45 cycles of 95°C for 10 s, 60°C for 30 s and 72°C for 20 s. The expression of target genes was calculated using 2 −ΔΔCt method.…”
Section: Methodsmentioning
confidence: 99%
“…The circadian clock is essential for the maintenance of homeostasis during a diverse of physiological processes, such as sleep-wake cycle, feeding-fasting rhythm, rhythmic change of body temperature, levels of hormones, levels of glucose and lipid, et al 10 , 11 . Recently, the regulatory function of circadian clock on cellular fate has been concerned 12 , 13 . REV-ERBα is a core ingredient of circadian clock and acts as a repressor in maintaining the circadian clock 14 .…”
Section: Introductionmentioning
confidence: 99%